Buddhism, War, and Nationalism Chinese Monks in the Struggle Against Japanese Aggression 1931-1945. - Yu, Xue. (Hoboken : Taylor and Francis, 2013)
This thesis examines the doctrinal grounds and different approaches to working out this ""new Buddhist tradition, "" a startling contrast to the teachings of non-violence and compassion which have made Buddhism known as a religion of peace. In scores of articles as war approached in 1936-37, new monks searched and reinterpreted scripture, making controversial arguments for ideas like ""compassionate killing"" which would justify participating in war.
Cover; Title; Copyright; Dedication; Contents; Foreword; Acknowledgments; Introduction; Chapter One Changing Buddhism in Modern China; Chapter Two Buddhism and National Defending; Chapter Three Propaganda against Japanese Aggressions; Chapter Four Buddhist Participation in the War; Chapter Five Buddhism in Japanese-Occupied Areas; Chapter Six Taixu and Buddhism after the War; Conclusion; Notes; Bibliography; Index.
Description based on print version record.
Keywords: Buddhism -- Social aspects -- China; Sino-Japanese War, 1937-1945.; War -- Religious aspects; Buddhism -- Social aspects -- China; Sino-Japanese War, 1937-1945.; War -- Religious aspects -- Buddhism; RELIGION / Comparative Religion; Electronic books